Impacts of Spotlight Effect on Performance Anxiety and Self-Confidence Among Athletes in University of Port Harcourt - Ochor Daniel Chinonso (Wah Academia Journal of Social Sciences, 2025)
This study investigates the impacts of the spotlight effect on performance anxiety and self-confidence among athletes in University of Port Harcourt. The spotlight effect refers to the tendency of individuals to over-estimate the extent to which they are the focus of others’ attention, which can lead to heightened anxiety and diminished confidence, especially in competitive sports environments. The research employed a quantitative approach, using a structured questionnaire divided into four sections: demographic information, performance anxiety, self-confidence, and coping strategies. The sample size consisted of 60 undergraduate athletes, both male and female, representing various sports disciplines. Data were analyzed using descriptive statistics, independent t-tests, and one-way ANOVA to assess differences based on gender and sport type (team vs. individual). The findings revealed a significant relationship between the spotlight effect and increased performance anxiety, with male athletes experiencing higher levels of anxiety compared to females. Additionally, athletes participating in individual sports reported lower self-confidence under the spotlight effect than those involved in team sports. The analysis of coping strategies highlighted that athletes employ various techniques, including relaxation exercises, mental visualization, and peer support, to mitigate the negative impacts of the spotlight effect. The study concludes that the spotlight effect significantly influences athletes’ psychological states, affecting their anxiety levels and self-confidence, with notable differences across gender and sport type. It recommends targeted mental training programs, gender-specific support, and simulation of high-pressure environments to help athletes manage the pressures of being observed during competition. These interventions could contribute to improving overall athletic performance and well-being.